Calpain-1 weakens the nuclear envelope and promotes the release of neutrophil extracellular traps - Singh, Jeeshan; Zlatar, Leticija; Munoz Becerra, Marco; Lochnit, Günter; Herrmann, Irmgard; Pfister, Felix; Janko, Christina; Knopf, Jasmin; Leppkes, Moritz; Schoen, Janina; Munoz, Luis Enrique; Schett, Georg; et al. (Cell Communication and Signaling, 2024)
The inducers of neutrophil extracellular trap (NET) formation are heterogeneous and consequently, there is no specific pathway or signature molecule indispensable for NET formation. But certain events such as histone modification, chromatin decondensation, nuclear envelope breakdown, and NET release are ubiquitous. During NET formation, neutrophils drastically rearrange their cytoplasmic, granular and nuclear content. Yet, the exact mechanism for decoding each step during NET formation still remains elusive. Here, we investigated the mechanism of nuclear envelope breakdown during NET formation. Immunofluorescence microscopic evaluation revealed a gradual disintegration of outer nuclear membrane protein nesprin-1 and alterations in nuclear morphology during NET formation. MALDI-TOF analysis of NETs that had been generated by various inducers detected the accumulation of nesprin-1 fragments. This suggests that nesprin-1 degradation occurs before NET release. In the presence of a calpain-1, inhibitor nesprin-1 degradation was decreased in calcium driven NET formation. Microscopic evaluation confirmed that the disintegration of the lamin B receptor (LBR) and the collapse of the actin cytoskeleton occurs in early and later phases of NET release, respectively. We conclude that the calpain-1 degrades nesprin-1, orchestrates the weakening of the nuclear membrane, contributes to LBR disintegration, and promoting DNA release and finally, NETs formation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Calpain-1; Nesprin-1; Neutrophil extracellular traps (NETs); Nuclear envelope break down

Neutrophil Extracellular Traps Drive Dacryolithiasis - Zlatar, Leticija; Timm, Thomas; Lochnit, Günter; Bilyy, Rostyslav; Bäuerle, Tobias; Munoz Becerra, Marco; Schett, Georg; Knopf, Jasmin; Heichel, Jens; Ali, Mohammad Javed; Schapher, Mirco; Paulsen, Friedrich; et al. (Cells, 2023)
Mucopeptide concretions, previously called dacryoliths, are macroscopic stones that commonly obstruct the lacrimal sac. The mechanism behind dacryolithiasis remains unclear; however, the involvement of various immune cells, including neutrophils, has been confirmed. These findings remain limited, and no information on neutrophil extracellular traps (NETs), essentially involved in the pathogenesis of other lithiases, is available yet. Here, we employ microcomputed tomography, magnetic resonance tomography, histochemistry, mass spectrometry, and enzyme activity analyses to investigate the role of neutrophils and NETs in dacryolithiasis. We classify mucopeptide concretions into three types, with respect to the quantity of cellular and acellular material, polysaccharides, and mucosubstances. We propose the role of neutrophils and NETs within the existing model of gradual formation and growth of mucopeptide concretions, with neutrophils contributing to the initial stages of dacryolithiasis, as they localized on the inner (older) parts of the tissue. As NETs localized on the outer (newer) parts of the tissue, we link their role to the late stages of dacryolithiasis, presumably maintaining the proinflammatory environment and preventing efficient clearance. An abundance of IgG on the surface indicates the involvement of the adaptive immune system later as well. These findings bring new perspectives on dacryolithiasis, in which the innate and adaptive immune system are essentially involved.
CRIS-Team Scopus Importer:2023-08-11
Keywords: dacryolithiasis; dacryoliths; lacrimal sac; mucopeptide concretions; neutrophil extracellular traps; neutrophils

Neutrophils seeking new neighbors: radiotherapy affects the cellular framework and the spatial organization in a murine breast cancer model - Reichardt, Clara; Munoz Becerra, Marco; Rius Rigau, Aleix Rius; Rückert, Michael; Fietkau, Rainer; Schett, Georg; Gaipl, Udo; Frey, Benjamin; Munoz Becerra, Luis (Cancer Immunology, Immunotherapy, 2024)
Neutrophils are known to contribute in many aspects of tumor progression and metastasis. The presence of neutrophils or neutrophil-derived mediators in the tumor microenvironment has been associated with poor prognosis in several types of solid tumors. However, the effects of classical cancer treatments such as radiation therapy on neutrophils are poorly understood. Furthermore, the cellular composition and distribution of immune cells in the tumor is of increasing interest in cancer research and new imaging technologies allow to perform more complex spatial analyses within tumor tissues. Therefore, we aim to offer novel insight into intra-tumoral formation of cellular neighborhoods and communities in murine breast cancer. To address this question, we performed image mass cytometry on tumors of the TS/A breast cancer tumor model, performed spatial neighborhood analyses of the tumor microenvironment and quantified neutrophil-extracellular trap degradation products in serum of the mice. We show that irradiation with 2 × 8 Gy significantly alters the cellular composition and spatial organization in the tumor, especially regarding neutrophils and other cells of the myeloid lineage. Locally applied radiotherapy further affects neutrophils in a systemic manner by decreasing the serum neutrophil extracellular trap concentrations which correlates positively with survival. In addition, the intercellular cohesion is maintained due to radiotherapy as shown by E-Cadherin expression. Radiotherapy, therefore, might affect the epithelial–mesenchymal plasticity in tumors and thus prevent metastasis. Our findings underscore the growing importance of the spatial organization of the tumor microenvironment, particularly with respect to radiotherapy, and provide insight into potential mechanisms by which radiotherapy affects epithelial–mesenchymal plasticity and tumor metastasis.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Cancer; Cellular neighborhood; Image mass cytometry; Neutrophil; Radiotherapy

Suppression of neutrophils by sodium exacerbates oxidative stress and arthritis - Zlatar, Leticija; Mahajan, Aparna; Munoz Becerra, Marco; Weidner, Daniela; Bila, Galyna; Bilyy, Rostyslav; Titze, Jens; Hoffmann, Markus H.; Schett, Georg; Herrmann, Martin; Steffen, Ulrike; Muñoz, Luis E.; et al. (Frontiers in Immunology, 2023)
Introduction: Typical Western diet, rich in salt, contributes to autoimmune disease development. However, conflicting reports exist about the effect of salt on neutrophil effector functions, also in the context of arthritis. Methods: We investigated the effect of sodium chloride (NaCl) on neutrophil viability and functions in vitro, and in vivo employing the murine K/BxN-serum transfer arthritis (STA) model. Results and discussion: The effects of NaCl and external reactive oxygen species (H2O2) were further examined on osteoclasts in vitro. Hypertonic sodium-rich media caused primary/secondary cell necrosis, altered the nuclear morphology, inhibited phagocytosis, degranulation, myeloperoxidase (MPO) peroxidation activity and neutrophil extracellular trap (NET) formation, while increasing total ROS production, mitochondrial ROS production, and neutrophil elastase (NE) activity. High salt diet (HSD) aggravated arthritis by increasing inflammation, bone erosion, and osteoclast differentiation, accompanied by increased NE expression and activity. Osteoclast differentiation was decreased with 25 mM NaCl or 100 nM H2O2 addition to isotonic media. In contrast to NaCl, external H2O2 had pro-resorptive effects in vitro. We postulate that in arthritis under HSD, increased bone erosion can be attributed to an enhanced oxidative milieu maintained by infiltrating neutrophils, rather than a direct effect of NaCl.
CRIS-Team Scopus Importer:2023-09-01
Keywords: K/BxN serum transfer arthritis; neutrophil extracellular traps (NETs); neutrophils; osteoclasts; reactive oxygen species; sodium chloride